2018
DOI: 10.3390/plants8010008
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the Axes: A Lesson from the Root

Abstract: How the body plan is established and maintained in multicellular organisms is a central question in developmental biology. Thanks to its simple and symmetric structure, the root represents a powerful tool to study the molecular mechanisms underlying the establishment and maintenance of developmental axes. Plant roots show two main axes along which cells pass through different developmental stages and acquire different fates: the root proximodistal axis spans longitudinally from the hypocotyl junction (proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…PHB and PHV Control MC Formation via the Regulation of the CYCLIN D6;1 (CYCD6;1) Expression Domain In Arabidopsis, expression of PHABULOSA (PHB) and of its redundant homologous PHAVOLUTA (PHV) is restricted to the vascular tissue due to the repressive activity of microRNA165 (miRNA165) and 166 in the ground tissue (GT). [8][9][10] We have recently shown that miR165-and 166-resistant mutants of PHB and PHV (phb-1d and phv-1d, respectively), where PHB and PHV are present also in the GT, have supernumerary cortex formation already during early phase of root development, suggesting that these transcription factors regulate GT patterning. 11 Because Arabidopsis plants acquire an additional cortical layer in late post-embryonic root development ( Figures 1A and 1B), we assessed whether PHB and PHV control middle cortex (MC) formation analyzing MC development in phb,phv loss-of-function plants (phb-13, phv-11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHB and PHV Control MC Formation via the Regulation of the CYCLIN D6;1 (CYCD6;1) Expression Domain In Arabidopsis, expression of PHABULOSA (PHB) and of its redundant homologous PHAVOLUTA (PHV) is restricted to the vascular tissue due to the repressive activity of microRNA165 (miRNA165) and 166 in the ground tissue (GT). [8][9][10] We have recently shown that miR165-and 166-resistant mutants of PHB and PHV (phb-1d and phv-1d, respectively), where PHB and PHV are present also in the GT, have supernumerary cortex formation already during early phase of root development, suggesting that these transcription factors regulate GT patterning. 11 Because Arabidopsis plants acquire an additional cortical layer in late post-embryonic root development ( Figures 1A and 1B), we assessed whether PHB and PHV control middle cortex (MC) formation analyzing MC development in phb,phv loss-of-function plants (phb-13, phv-11).…”
Section: Resultsmentioning
confidence: 99%
“…Please cite this article in press as: Bertolotti et al, A PHABULOSA-Controlled Genetic Pathway Regulates Ground Tissue Patterning in the Arabidopsis Root, Current Biology (2020), https://doi.org/10.1016/j.cub.2020. 10…”
Section: Ll Open Accessmentioning
confidence: 99%
“…For root length measurements, plates were photographed and the resulting images were analyzed using the analysis software ImageJ 1.47v available online (https://imagej.nih.gov/ij/). Root meristem size of 5 days post germination plants was measured based on the number of cortex cells in a file extending from the quiescent center to the first elongated cortex cell excluded, as described previously [38][39][40]. Images were obtained using a confocal laser scanning microscope (Zeiss LSM 780).…”
Section: Root Length Meristem Size and Cell Size Analysismentioning
confidence: 99%
“…Organ growth in plants is supported by the meristems, regions providing a reservoir of undifferentiated cells whose activity depends on the stem cell niche [1]. In the root, the stem cells daughters proliferate establishing the division zone of the meristem and, more distally from the root tip along the longitudinal axis, those cells differentiate generating the differentiation zone [2,3,4,5]. The boundary between proliferating and differentiating cells is called transition zone (TZ).…”
Section: Introductionmentioning
confidence: 99%